2004
DOI: 10.1593/neo.03439
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Analysis of Gene Copy Number Alterations in Human Prostate Cancer Using CGH on cDNA Microarrays: Impact of Copy Number on Gene Expression

Abstract: Identification of target genes for genetic rearrangements in prostate cancer and the impact of copy number changes on gene expression are currently not well understood. Here, we applied high-resolution comparative genomic hybridization (CGH) on cDNA microarrays for analysis of prostate cancer cell lines. CGH microarrays identified most of the alterations detected by classic chromosomal CGH, as well as a number of previously unreported alterations. Specific recurrent regions of gain (28) and loss (18) were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
50
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(59 citation statements)
references
References 18 publications
9
50
0
Order By: Relevance
“…Among these 23 tumor samples with combined TRAF4 gene amplification and overexpression, 17 (74%) showed a strong TRAF4 immunostaining (2 þ ), which suggests that increased TRAF4 gene copy number is associated to higher level of TRAF4 protein expression. Aside from high levels of amplification of known oncogenes, genome-wide analysis of gene copy number alterations in cancer revealed that the majority of transcriptional variations are due to low level copy number changes (Hyman et al, 2002;Wolf et al, 2004). In our study, the TRAF4 gain observed in 22% of all cases was moderate (up to 10 copies) but it was significantly associated with gene expression.…”
supporting
confidence: 45%
“…Among these 23 tumor samples with combined TRAF4 gene amplification and overexpression, 17 (74%) showed a strong TRAF4 immunostaining (2 þ ), which suggests that increased TRAF4 gene copy number is associated to higher level of TRAF4 protein expression. Aside from high levels of amplification of known oncogenes, genome-wide analysis of gene copy number alterations in cancer revealed that the majority of transcriptional variations are due to low level copy number changes (Hyman et al, 2002;Wolf et al, 2004). In our study, the TRAF4 gain observed in 22% of all cases was moderate (up to 10 copies) but it was significantly associated with gene expression.…”
supporting
confidence: 45%
“…8,39 The increase in mRNA level caused by amplification is not always proportional to the number of gene copies; 33 and the effects of the gene copy number on expression levels were more relevant for high-level amplifications in a gene-by-gene analysis; results that were also found in breast and prostate cancers. 40,41 In our series, only the cases with dmin amplification, present in more than 10% of the cells, showed an increase of RNA expression.…”
Section: Discussionmentioning
confidence: 47%
“…MALDI-TOF MS-based identification of the nuclear proteins bound to ANXA7-promoter (F, À1086/À890) in prostate cancer (PC3) versus normal prostate cells (PrEC) The more abundant bands in the DNA-affinity pattern for the F-segment in PC3 (as shown in Figure 3) correspond to the uniquely high ANXA7 gene copy number (Wolf et al, 2004) and complementary DNA (cDNA) expression in PC3 among other NCI-60 cells (Stanford Microarray Database, Stanford, CA, USA, as shown in Supplementary Figure S1). Accordingly, PC3 shows greater than threefold increase of ANXA7 protein expression compared with other tested cells, including PrEC, DU145, and LNCaP (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, although the specifically high gene copy number of ANXA7 (Wolf et al, 2004) can explain the increase in total gene and protein expression of ANXA7 in PC3, multiple ANXA7 products in PC3 versus PrEC indicate additional hnRNP-associated effects on ANXA7 splicing in PC3. According to ANXA7 expression profiling in cancer cells (Gene Expression Omnibus and Stanford Microarray Database), only PC3 and PPC-1 cells, that share similar karyotypes, have ANXA7 elevation, and an ANXA7 expression profile in general is not concordant with hnRNPs ( Supplementary Figure S2-S3).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation